Pengaruh Kepemimpinan dan Lingkungan Kerja terhadap Kinerja Pegawai pada Kantor Pelayanan Pajak Daerah DIY di Kabupaten Gunungkidul - Puji Lestari (UPAJIWA, 2019)
This study aims to determine the effect of Leadership and Work Environment on Employee Performance at DIY Regional Tax Office in Gunungkidul Regency with Motivation as an Intervening Variable. The object of this research is all of the 39 KPPD District Gunungkidul Regency employees. The method of data collection in this study was conducted by using a questionnaire (questionnaire). The data analysis method used in this study is Partial Least Square (PLS) with SmartPLS 3.2.7 software. The results in this study Leadership has a significant effect on motivation but does not have a significant effect on employee performance. The work environment has a significant effect on employee motivation and performance. Motivation does not significantly influence employee performance. Leadership and work environment simultaneously influence employee motivation and performance. significant effect on performance through motivation, work environment has a significant effect on employee performance through motivation. Performance influenced by leadership, work environment and motivation is only 41.1% Keywords: Leadership, Work Environment, Employee Performance, Motivation